2024
DOI: 10.3389/fneur.2023.1331604
|View full text |Cite
|
Sign up to set email alerts
|

The association between high jugular bulb and mastoid pneumatization in adults

Chenyu Chen,
Simin Weng,
Zhifeng Chen
et al.

Abstract: PurposeThe purpose of this study was to analyze the relationship between the degree of high jugular bulb (HJB) and mastoid pneumatization using high-resolution computed tomography (HRCT).MethodsBetween April 2019 and June 2022, HRCT of the temporal bone was retrospectively analyzed in 1,025 patients. By excluding the other coexistent pathologies, 113 patients with HJBs were recruited for the study. The degree of the HJBs were defined as follows: Grade I, JB situated between inferior annulus of tympanic membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“…In contrast, Aladeyelu et al [ 1 ] found HJB across various pneumatization degrees, notably more prevalent in cases of hyper-pneumatized temporal bone, indicating a significant pattern at p < .001. This diverges from Chen et al‘s findings [ 7 ], which aligned with Orr et al [ 30 ] in noting no marked difference in mastoid air cell volume between severe and mild HJB cases, highlighting no direct link between JB positioning and pneumatization extent. However, Orr et al observed a reliable correlation between certain anatomical distances around the JB, suggesting some degree of spatial consistency regardless of pneumatization.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast, Aladeyelu et al [ 1 ] found HJB across various pneumatization degrees, notably more prevalent in cases of hyper-pneumatized temporal bone, indicating a significant pattern at p < .001. This diverges from Chen et al‘s findings [ 7 ], which aligned with Orr et al [ 30 ] in noting no marked difference in mastoid air cell volume between severe and mild HJB cases, highlighting no direct link between JB positioning and pneumatization extent. However, Orr et al observed a reliable correlation between certain anatomical distances around the JB, suggesting some degree of spatial consistency regardless of pneumatization.…”
Section: Discussioncontrasting
confidence: 84%